STUDI PEMBUATAN DODOL PISANG (Musa paradisiaca L) - Muhammad Iqbal Nusa; Misril Fuadi; Winda Astari Putri Pulungan (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2012)
This study aimed to determine the effect of the concentration of sugar and agar concentration on the quality of banana lunkhead. This research used Completely Randomized Design (CRD) factorial with (2) two replications. The first factor is the concentration of sugar with a password (G) which consists of four levels, namely: G1 = 20%, G2 = 30%, G3 and G4 = 40% = 50%. Second factor is the concentration of gelatin with a password (A) which consists of 4 levels are: A1 = 3.0%, A2 = 3.5%, 4.0% and A3 = A4 = 4.5%. The parameters observed were: TSS, moisture content, texture, color, flavor and aroma. Statistical Result analysis on each parameter gives the following conclusion: sugar concentrations highly significant effect (p> 0.01) in the TSS. Agar concentrations highly significant effect (p> 0.01) in the TSS. Sugar concentrations highly significant effect (p> 0.01) in the moisture content. Agar concentrations highly significant effect (p> 0.01) in the moisture content. Effect of different concentrations of glucose did not significantly (p <0.05) to the texture. Agar concentrations highly significant effect (p> 0.01) in the texture. Sugar concentrations highly significant effect (p> 0.01) on the color. Sugar concentrations highly significant effect (p> 0.01) in the flavor and aroma. 3,550 highest flavor and aroma obtained at treatment G4, G1 lowest at 2,425. Agar concentrations highly significant effect (p> 0.01) for flavor and aroma. Flavor and aroma highest obtained at treatment A4 3.363, 2.613 lowest on the A1. Keyword: concentration of sugar, agar concentration, quality of banana